EKONOMI MAKRO ISLAM : PERTUMBUHAN DAN PERKEMBANGAN DI INDONESIA - Asy Sya’Bany, Ghulam; Adi Cahyo, Wisnu Handika; Karomah, Ummul; Sa’diyah, Hikmatus; Latifah, Eny (JISEF : Journal Of International Sharia Economics And Financial, 2023)
This article aims to find out how the development and growth of macroeconomics in Indonesia.. Evaluation and analysis of economic performance of a country or region for a certain period of time known as a review of economic growth. This is done to understand how well the economic policy is applied and to find which part needs to be repaired or adjusted. The Macro Economy of Syariah is an economic branch that focuses on the principles of Islamic economics to achieve wholeness, prosperity, and prosperity as a whole. The contribution of the Macro Economic Sharia includes several important aspects: financial stability, financial inclusion, distribution of sustainable economic growth and growth. The Islamic economy has great potential to develop and provide an ethical and sustainable alternative in the global economy world. The economic development in an Islamic perspective involves various principles and concepts that aim to create sustainable and fair welfare. And several pillars of economic development in Islamic perspectives. Refuse of economic growth is various indicators used to measure the extent to which the economy of a country or region develops over time.